Cobalt-Catalyzed Hydroboration and Borylation of Alkenes and Alkynes - Zuo, Ziqing; Wen, Huanan; Liu, Guixia; Huang, Zheng (Synlett, 2018)
Incorporation of the boryl moiety across a carbon–carbon multiple bond is a powerful method for the synthesis of organoboron compounds. This kind of transformation could be realized with high chemo-, regio-, and stereoselectivity by using an appropriate transition-metal catalyst. This account summarizes the latest advances from our group in the area of cobalt-catalyzed hydroboration and borylation of alkenes and alkynes, which lead to the formation of a variety of organoboron compounds, including alkylboronates, 1,1,1-tris(boronates), 1,1-diborylalkenes, and 1,1-diboronates.1 Introduction2 Cobalt-Catalyzed Hydroboration of Alkenes3 Cobalt-Catalyzed Dehydrogenative Borylations-Hydroboration4 Cobalt-Catalyzed Double Dehydrogenative Borylations of 1-Alkenes5 Cobalt-Catalyzed Hydroboration of Terminal Alkynes6 Summary and Outlook
Keywords: alkenes; alkynes; borylation; cobalt; organoboronates